State formation and identity in the Middle East and North Africa - Christie, Kenneth; Masad, Mohammad; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2013)
For states in the Middle East, North Africa, and South Asia, the'Arab Spring' has had different implications and consequences, stemming from the politics of identity and the historical and political processes that have shaped development. This book focuses on how these factors interact with globalization and affect state formation.
Keywords: Science; Science; Science, general